Dimensions of passion and their relationship to the risk of exercise addiction: Cultural and gender differences - Attila Szabo; Ricardo de la Vega; Rita Kovácsik; Lucia Jiménez Almendros; Roberto Ruíz-Barquín; Zsolt Demetrovics; Szilvia Boros; Ferenc Köteles (Addictive Behaviors Reports, 2022)
This study was performed to investigate further the two-dimensional aspect of passion and its relationship to the risk of exercise addiction (REA) in nine nations and to clarify the unresolved gender differences. The here reported results stem from the reanalysis of data gathered in three previous empirical studies. The analyses demonstrated that harmonious (HP) and obsessive (OP) passion are two independent, non-interacting predictors of the REA, the prevalence of which was 12.1 % in the current sample that included 1448 people (age = 30.49 ± SD = 11.17 years; 55 % men), who exercised at least three hours per week. Furthermore, the results show that HP and OP could co-exist as a single ‘total’ or ‘true’ passion within the individual or in high-low HP and OP proportions, supporting the proposal for one, two-dimensional passion. Indeed, most people at REA demonstrated both high HP and high OP. The weekly amount of exercise was weakly associated with the two dimensions of passion. Relatively specific cultural differences in the REA and OP, but not HP, have emerged. The results also demonstrate that when a minimal weekly volume of training (i.e., 3 h) is a criterion for participant recruitment, no gender differences occur in the REA.